Design of a lesson plan in the context of stem education for perspective primary school teachers - Есназар, Асель; Zhorabekova A.N.; Uristenbekova G.K.; Koshkarova Madina; Nurmakhambetova Assel (Pedagogy and Psychology, 2024)
The problem of organizing and implementing the educational process in the context of STEM education is one of the most pressing topics. In determining the relevance of the article, the issues of STEM education based on the methodological recommendations of the National Academy of education, integrated educational programs provided for in programs aimed at the development of education and science, an interdisciplinary approach were analyzed. In addition, a review of the research of domestic and foreign scientists who studied the concepts of "interdisciplinary communication", "integration", "STEM education" was carried out. The purpose of the article is to develop a lesson plan in the context of stem education for future primary school teachers. The experimental study was selected from among the students of the South Kazakhstan Pedagogical University named after Uzbekali Zhanibekov, and the selection group was randomly selected from among the fourth - year students of the educational program 6B01301 - "training of a teacher of pedagogy and methods of primary education". One of the students was identified as a control group (19 students), the other as an experimental group (22 students). Three stages of experimental work (detection, formation, control) were implemented. In the course of the study, the method of survey and descriptive statistics was used. The study was conducted in the fall semester of the 2023-2024 academic year. At the formation stage, a 12-hour seminar was organized aimed at developing a lesson plan in the context of stem education for future primary school teachers. As a result of the study, the indicators of experimental work at the control stage showed that the work organized at the formation stage was productive.